Maternal Behavioral Determinants of Oral Hygiene Status among Preschool Children: Evidence from a Community-Based Cross-Sectional Study in Pidie Jaya - Reca Reca; Teuku Salfiyadi; Cut Aja Nuraskin; Henny Febriani; Eka Sri Rahayu (PT. Riset Press International, 2026)
Oral health plays a fundamental role in maintaining overall systemic health, as poor oral conditions may contribute to broader health complications. Among the various determinants of children’s oral health, maternal knowledge and behavior represent critical influencing factors, particularly during early childhood when children are highly dependent on parental guidance. Preliminary observations in Meugit Sagoe Village indicated that a substantial proportion of children aged 3–5 years (75%) exhibited poor oral hygiene status, highlighting the urgency of addressing this public health concern. This study aimed to examine the association between maternal behavior and the oral hygiene status of children in Meugit Sagoe Village. An analytical observational design with a cross-sectional approach was employed. The study sample consisted of 40 mother–child pairs selected through purposive sampling based on predefined inclusion criteria. Data collection was conducted using a combination of clinical dental examinations to assess children’s oral hygiene status and structured interviews to evaluate maternal behavior. The instruments utilized included a standardized dental diagnostic set and a validated questionnaire. Statistical analysis was performed using the Statistical Package for the Social Sciences (SPSS). The association between variables was analyzed using the Chi-square test, with a significance level set at α = 0.05. The results demonstrated a statistically significant relationship between maternal behavior and children’s oral hygiene status (p = 0.003). These findings indicate that maternal knowledge and behavior are significantly associated with the oral hygiene condition of children. This study contributes to the growing body of evidence emphasizing the importance of maternal factors in shaping oral health outcomes during early childhood. Specifically, it provides empirical support for the role of maternal knowledge, attitudes, and practices as key determinants of oral hygiene status among preschool children. The findings highlight the need for family-centered oral health promotion programs that actively involve mothers as primary caregivers in fostering healthy oral hygiene behaviors. Furthermore, this study offers practical implications for policymakers and healthcare professionals in designing targeted educational and preventive interventions aimed at improving maternal awareness and reducing the burden of oral diseases among young children.